2015
DOI: 10.4103/1008-682x.136443
|View full text |Cite
|
Sign up to set email alerts
|

Inguinal and subinguinal micro-varicocelectomy, the optimal surgical management of varicocele: a meta-analysis

Abstract: Conventional meta-analyses have shown inconsistent results for the efficacy of various treatments of varicoceles. Therefore, we performed a multiple-treatment meta-analysis to assess the effectiveness and safety of 10 methods of varicocelectomy and embolization/sclerotherapy. We systematically reviewed 35 randomized controlled trials and observational studies, from 1966 to August 5, 2013, which compared any of the following treatments for varococeles: laparoscopic, retroperitoneal, open inguinal and subinguina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(17 citation statements)
references
References 48 publications
1
15
0
1
Order By: Relevance
“…They also clearly highlighted the impact of varicocele treatment on all semen parameters (compared to controls, OR = 12.3 (9.45 – 15.19) for sperm concentration, 0.86 (7.07 – 14.65) for total motility, 9.69 (4.86 – 14.52) for progressive motility [5]. This positive impact of varicocele treatment on semen parameters has been supported by two recent meta-analyses [22, 23]. Moreover, Baazzem et al included in their study new interesting end points that were not analyzed previously, and that were improved following the treatment (oxidative stress, sperm DNA damage, sperm ultrastructure) [5].…”
Section: Discussionmentioning
confidence: 70%
“…They also clearly highlighted the impact of varicocele treatment on all semen parameters (compared to controls, OR = 12.3 (9.45 – 15.19) for sperm concentration, 0.86 (7.07 – 14.65) for total motility, 9.69 (4.86 – 14.52) for progressive motility [5]. This positive impact of varicocele treatment on semen parameters has been supported by two recent meta-analyses [22, 23]. Moreover, Baazzem et al included in their study new interesting end points that were not analyzed previously, and that were improved following the treatment (oxidative stress, sperm DNA damage, sperm ultrastructure) [5].…”
Section: Discussionmentioning
confidence: 70%
“…On the contrary, a non-RCT including 91 infertile males with bilateral clinical varicocele (grades 2 to 3 on the left side and grade 1 on the right side) indicated that bilateral varicocelectomy was superior to left varicocelectomy in total sperm count, sperm concentration and motility (Scherr & Goldstein, 1999). Thus, the treatment of (Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis published by Wang et al . 13 showed that ASS and microsurgical repair are superior to other techniques (open retroperitoneal surgery, laparoscopic approach) in terms of hydrocele formation. The lower risk of hydrocele formation for ASS in comparison with open surgical approach was previously highlighted by a randomized prospective study.…”
Section: Discussionmentioning
confidence: 99%